EFEKTIVITAS MEDIA FLANELGRAPH UNTUK MENINGKATKAN KEMAMPUAN OPERASI PENJUMLAHAN BAGI TUNARUNGU - Arifia Yunita Lisa (Jurnal Penelitian Pendidikan Khusus, 2012)
This research, using approach of experiment in the form of Single Subject Research (SSR) by wearing to be designed A-B-A. As its of him is one child people of tunarungu. Condition of baseline 1 (A1) is condition of early had by child with child value 3 and used time 20 minute, and mount to become 10 with time 15 minute at condition of intervention ( B) by using media of flanelgraph, after time interval passed to baseline second (A2) without using media assess child 10 and used time 13 minute.